Toowoomba to Millmerran Pipeline ù Sustainable Development Through Reusing Effluent for Industrial and Mining Processes - B McCreath (The Australasian Institute of Mining and Metallurgy, 2003)
Industrial process water for the Commodore Coal Mine and the adjoining Millmerran Power Station is provided by pumping secondary treated sewage effluent 100 km from the Wetalla Sewage Treatment Plant near Toowoomba. (A separate source is used for potable water.) The effluent is not of sufficient quality for discharge to a watercourse, but it is suitable, with further treatment, for the mine and power station. In designing and constructing the pipeline, special emphasis was placed on preventing accidental spills or planned releases to the environment. The pipeline and associated works can transfer 1000 ML/annum for reuse in the coal mine and power station.